International express Intermediate MultiPACK C - Harding, Keith (Oxford University press, 2010)
Unit 9-12: Time clauses; 1st & 2nd conditionals; Present perfect simple, Present perfect continuous. Time phrases; 3rd conditional; Reporting spoken language; Anh văn Hội Việt Mỹ tặng